Distribution and Movements of the Teshekpuk Caribou Herd 1990–2005: Prior to Oil and Gas Development - Person, Brian T.; Prichard, Alex K.; Carroll, Geoffry M.; Yokel, David A.; Suydam, Robert S.; George, John C. (ARCTIC, 2009)
Four caribou (Rangifer tarandus grantii) herds calve on the North Slope of Alaska, three of which have been exposed to little or no resource development. We present 15 years of baseline data on the distribution and movements of 72 satellite-collared and 10 GPS-collared caribou from the Teshekpuk caribou herd (TCH) that have had little to no exposure to oil and gas activities. Fixed-kernel home range analyses of collared caribou revealed that calving grounds were concentrated (i.e., 50% kernel utilization distribution) along the northeastern, eastern, and southeastern shores of Teshekpuk Lake. During the postcalving period, 51% and 35% of caribou moved through two constricted zones to the east and west of Teshekpuk Lake, respectively, and accessed insect-relief habitat along the Beaufort Sea coast. During late summer and early fall, TCH caribou were concentrated to the southeast and southwest of Teshekpuk Lake. Although 65% of the Teshekpuk caribou wintered in two areas on the central coastal plain around the village of Atqasuk and south of Teshekpuk Lake, other TCH animals wintered in a great variety of places, including the Seward Peninsula, the eastern and southern Brooks Range, and the Arctic National Wildlife Refuge. We detected an apparent emigration rate of 6.9%. One male and five female TCH caribou joined the breeding populations of the Western Arctic and Central Arctic herds. TCH caribou traveled an average distance of 2348 ± 190 km annually. Movement rates were at a maximum in midsummer, lowest in winter, and intermediate during spring and fall migrations. Restrictions on oil and gas leasing and surface occupancy have been in place to protect calving, migratory corridors, and insect-relief habitat for the TCH, but these protections are likely to be removed. These data will provide a good baseline that can be used to compare predevelopment distribution and movement patterns of TCH caribou to distribution and movement patterns during and after petroleum development. Quatre hardes de caribous (Rangifer ...